Evaluation of the efficacy of freeze-dried bovine pericardium and acellular bovine skin in the treatment of diaphragmatic hernia in dogs - Osama H. Al-Hyani; Sahar M. Ibrahim; Abdullah M. Al-Saiegh (Iraqi Journal of Veterinary Sciences)
The article was designed to evaluate the efficiency of lyophilized bovine pericardium and acellular bovine skin for repairing diaphragmatic hernia in dogs. Twelve local breed adult dogs were used. In all animals, the diaphragmatic hernia was induced by removing 5cm diameter circular piece the diaphragm. The animals were divided into two equal groups (n=6). In the first group, the diaphragmatic hernia was repaired using lyophilized bovine pericardium, and in the second group, acellular bovine skin was applied. The results were evaluated studying the gross and histopathological changes on the 15th and 30th postoperative days. The gross results showed a different degree of adhesion at the site of hernial repair. The adhesion rate was developed more severely in the second group animals compared to the first group. The histopathological manifestation of the first group showed excessive and more mature granulation tissue formation with few inflammatory cell infiltrations with good angiogenesis comparable to the second group, which revealed moderate granulation tissue formation and blood vessel formation with sever infiltration of inflammatory cells. In conclusion, we can use lyophilized bovine pericardium and acellular bovine skin to repair diaphragmatic hernias in dogs, although lyophilized bovine pericardium is regarded as the best option despite its high cost.